2020
DOI: 10.3390/f11020177
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey of Wild Edible Fruit Tree Species in Lowland Areas of Ethiopia

Abstract: This study aimed to provide baseline information about wild edible tree species (WETs) through surveying of different ethnic groups in dryland areas in Ethiopia. Here the data about WETs are scant, and WETs status is unexplained under the rampant habitat degradation. Use forms, plant parts used, status, ethnobotanical knowledge, conservation needs as well as those threats affecting WETs were reviewed. The study identified 88 indigenous wild edible plants, of which 52 species were WETs. In most cases, fruits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 33 publications
5
42
0
1
Order By: Relevance
“…This is becoming more important as limited resources restrict food security initiatives in rural areas, despite an increased need for these programs in the face of changing climate and increasingly vulnerable smallholder farms [ 93 ]. Moreover, Dejene et al [ 94 ] suggested that due to the diversity of wild edible trees, conservation and management strategies are needed to achieve food security from the use of forest resources. Generally, the review confirmed that food security and agricultural policies have to focus on the contribution of wild edible foods as one pillar to food security.…”
Section: Inclusion Of Wild Edible Plants In Policy For Nutritionalmentioning
confidence: 99%
“…This is becoming more important as limited resources restrict food security initiatives in rural areas, despite an increased need for these programs in the face of changing climate and increasingly vulnerable smallholder farms [ 93 ]. Moreover, Dejene et al [ 94 ] suggested that due to the diversity of wild edible trees, conservation and management strategies are needed to achieve food security from the use of forest resources. Generally, the review confirmed that food security and agricultural policies have to focus on the contribution of wild edible foods as one pillar to food security.…”
Section: Inclusion Of Wild Edible Plants In Policy For Nutritionalmentioning
confidence: 99%
“…It is indicated that the plant is one of the main wild edible plants which is eaten during famine periods in most parts of the country. This indicated the availability of the plant while there is a drought for other plants [ 46 ]. It is also reported that Ximenia americana plant is one of the wild edible plants that could enhance food security in different parts of Ethiopia [ 47 – 49 ].…”
Section: Importance Of Ximenia Americana In Ethmentioning
confidence: 99%
“…The factors responsible as a cause are forest clearing, grazing, timber harvesting, charcoal making, drought and bark, and root harvesting. The most fearful thing about this plant is also the conservation status is very low as compared to other wild edible plants [ 46 ]. Previously, the plant was widely available in different parts of the country.…”
Section: Current Status Of Ximenia Americana Inmentioning
confidence: 99%
“…In addition, mushrooms can serve in a recreational context and in myths and beliefs [20]. Nutritionally, mushrooms are an important source of proteins, vitamins, fats, carbohydrates, amino acids, and minerals [21,22], i.e., they are a good alternative or substitute for meat and fish [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of documentation could make local mycological knowledge vulnerable [29]. Due to a continuing exodus of people from the countryside, local communities are gradually losing an important part of their traditional knowledge, particularly about wild mushroom species [24,26,29]. There is a genuine need to record and document local traditional knowledge and perceptions about useful wild mushrooms.…”
Section: Introductionmentioning
confidence: 99%